EVOLUTION OF MINERAL-FORMING FLUIDS AT THE 9-10° N AND 21° N EAST PACIFIC RISE HYDROTHERMAL SYSTEMS: FLUID INCLUSION DATA ON MINERALS - Bortnikov N.S.; Stavrova O.O.; Sagalevish A.M.; Simonov V.A.; Terenya E.O.; Dranichnikova V.V.; Ikorskii S.V.; Kamenskii I.L.; Avedisyan A.A. (My University, 2007)
Significant variations in temperature and chemical and isotopic composition were found by direct measurements in the mineral-forming fluids that make up sulfide mounds in the active hydrothermal fields confined to spreading centers [1, 2]. Sulfide–sulfate ores from a single source are precipitated over several tens of years, while physicochemical parameters vary more frequently than are measured. The study of fluid inclusions in the minerals from some sulfate–sulfide mounds revealed the wider variations in the mineral formation temperature and salinity of the mineral-forming fluids, as compared to those obtained by direct measurements in fluid seepages.